Thermal insulation of rice hull and waste polystyrene foam as a composite material - Flores, Franco C.; Orejudos, Jerson N.; Mostrales, Daniel S.; Empig, Vicente E. (2007)
This study is conducted to ascertain the insulation potential of waste materials, namely, rice hull and polystyrene foam combined, and assess their usefulness as alternative construction materials. It also attempts to determine the properties of the composite material such as Mass, Density and Thermal Conductivity Coefficient. Further, it ascertains whether there is a significant difference of temperature in the model building with and without the composite material installed.
Keywords: Thermal insulation; Composite materials; Mindanao studies